Differential expression of markers for endothelial cells, pericytes, and basal lamina in the microvasculature of tumors and granulation tissue. - Schlingemann, R. O. (1991)
The structure and function of the tumor microvasculature is of great interest for cancer biology, diagnosis, and therapy. The distribution of endothelial cells, pericytes, and basal lamina in tumors is not well documented. In this study, the authors investigated the distribution of markers for these different components in a series of malignant human tumors and in human granulation tissue, both situations with extensive angiogenesis. Their results show a striking heterogeneity in the expression of markers for pericytes and endothelial cells between different tumors, but also within a single tumor lesion. To be able to distinguish between these two adjacent cell types decisively, all marker studies were carried out both on the light and the electron microscopical level and compared with staining results in granulation tissue of cutaneous wounds in healthy volunteers and of decubitus lesions. In granulation tissue of decubitus lesions, well-defined zones with increasing levels of maturation can be delineated. It was found that antibodies recognizing von Willebrand factor often failed to stain the tumor capillaries. Of the pericyte markers, alpha-smooth muscle actin was only locally expressed by pericytes in the tumor vasculature, whereas the high-molecular-weight melanoma-associated antigen, a chondroitin sulfate proteoglycan, stained the microvasculature broadly. Staining of the basal lamina components collagen type IV and laminin was, within the tumor, not restricted to the microvasculature. From their findings the authors conclude that 1) for the visualization of the tumor vasculature, antibodies recognizing endothelial markers, especially monoclonal antibodies PAL-E and BMA 120, are preferable to those recognizing pericytes or basal lamina; 2) within the microvasculature of tumors and granulation tissue, a heterogeneity of expression of endothelial and pericyte markers is observed; 3) during the formation of granulation tissue, all three microvascular components can be demonstrated already in the histologically earliest stage, suggesting not only an involvement of endothelial cells but also of pericytes and basal lamina in the initial steps of angiogenesis in wound healing.